2023
DOI: 10.3389/fpls.2023.1250669
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the impact of biochar with different carbon/nitrogen ratios on soil biochemical properties and rhizosphere bacterial communities of flue-cured tobacco plants

Yingfen Yang,
Chenghu Ye,
Wei Zhang
et al.

Abstract: Background and aimsIn agriculture, biochar (BC) and nitrogen (N) fertilizers are commonly used for improving soil fertility and crop productivity. However, it remains unclear how different levels of BC and N fertilizer affect soil fertility and crop productivity.MethodsThis study elucidates the impact of different application rates of BC (0, 600, and 1200 kg/ha) and N fertilizer (105 and 126 kg/ha) on biomass accumulation, soil microbial biomass of carbon (SMC) and nitrogen (SMN), and soil biochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Biochar and fertilizer (base fertilizer) were thoroughly mixed into the soil in planting holes before transplanting seedlings. After field preparation, tobacco seedlings (50 days old) were transplanted in the planting holes on the ridges with plant × row spacings (60 cm × 120 cm) [ 28 ]. The experiment was conducted under five treatments: no BC (0 kg/ha; CK), 600 kg/ha BC (A1), 900 kg/ha BC (A2), 1200 kg/ha BC (A3), and 1800 kg/ha BC (A4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar and fertilizer (base fertilizer) were thoroughly mixed into the soil in planting holes before transplanting seedlings. After field preparation, tobacco seedlings (50 days old) were transplanted in the planting holes on the ridges with plant × row spacings (60 cm × 120 cm) [ 28 ]. The experiment was conducted under five treatments: no BC (0 kg/ha; CK), 600 kg/ha BC (A1), 900 kg/ha BC (A2), 1200 kg/ha BC (A3), and 1800 kg/ha BC (A4).…”
Section: Methodsmentioning
confidence: 99%
“…A study on Chinese cherries treated with tobacco straw BC revealed that genes related to phytohormones such as abscisic acid, indole acetic acid and gibberellins were regulated, and photosynthesis was also promoted [ 22 ]. Several studies have reported the growth-promoting effect of BC at lower dosages and the inhibition of growth at higher dosages [ 28 ], but the underlying molecular mechanisms are poorly understood. Therefore, transcriptomics may allow us to study key genetic factors and pathways involved in the growth promotion of tobacco under different BC application rates.…”
Section: Introductionmentioning
confidence: 99%
“…The soil samples were transported to the laboratory, where they were allowed to air dry at ambient temperature before being crushed and put through a 2 mm screen. The methods of soil physical and chemical analysis (1978;Yang et al, 2023) were followed in performing the soil physicochemical analysis. In particular, two stages of drying were used to measure the water content of the soil (per 100 g fresh weight).…”
Section: Soil Physicochemical Analysismentioning
confidence: 99%
“…The effect of biochar on soil physicochemical properties and plant growth varies depending on the nature and application rate of the biochar (Yang et al, 2023). Biochar amendment in the soil at a certain level can promote the growth and biomass of flue-cured tobacco, while higher application of biochar harms plant growth (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%